Antihypertensive and Antioxidant Effects of Functional Foods Containing Chia (Salvia hispanica) Protein Hydrolysates - Salazar-Vega, Ine M.; Segura-Campos, Maira R.; Chel-Guerrero, Luis A.; Betancur-Ancona, David A. (IntechOpen, 2012)
None